2015
DOI: 10.1007/s12149-015-1038-7
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET/CT for assessing the resectability of NSCLC patients with N2 disease after neoadjuvant therapy

Abstract: FDG PET/CT after neoadjuvant therapy accurately defined response in metastatic N2 nodes of NSCLC patients, presenting very high sensitivity and NPV for detecting responding nodes. PET/CT may enable selection of candidates for curative resection of stage III NSCLC. Mediastinoscopy may not be mandatory in patients with a negative PET/CT after neoadjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Previous studies also evaluated the value of 18 F-FDG PET/CT imaging after rising tumor markers or clinical suspicion of tumor recurrence, concluding that 18 F-FDG PET/CT is a good noninvasive imaging modality in these 2 settings to confirm or rule out tumor recurrences (4,12,29,30). Also, multiple studies confirmed the value of 18 F-FDG PET/CT scan in the therapy assessment setting after chemoradiation therapy in several cancer types (31)(32)(33).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies also evaluated the value of 18 F-FDG PET/CT imaging after rising tumor markers or clinical suspicion of tumor recurrence, concluding that 18 F-FDG PET/CT is a good noninvasive imaging modality in these 2 settings to confirm or rule out tumor recurrences (4,12,29,30). Also, multiple studies confirmed the value of 18 F-FDG PET/CT scan in the therapy assessment setting after chemoradiation therapy in several cancer types (31)(32)(33).…”
Section: Discussionmentioning
confidence: 94%
“…When N2 disease is suspected using PET-CT, neoadjuvant therapy instead of prompt surgery is considered as an initial treatment after pathological confirmation, if clinically feasible (7,9,10). Thus, PET-CT contributes to appropriate management of NSCLC by providing of qualitative and quantitative information from measuring lesion metabolic activity (1,12,14).…”
Section: Discussionmentioning
confidence: 99%
“…However, after neoadjuvant therapy, invasive mediastinal LN staging might be not needed because of frequent discrepancies between PET-CT and pathological findings, especially with previous mediastinal pathological staging (5,10). In addition, some studies show that DFS and OS are sufficiently high to warrant surgery for persistent N2 disease after neoadjuvant therapy (10,11,(19)(20)(21). We propose with caution that surgery should not be delayed or withheld only based on preoperative PET-CT findings after neoadjuvant therapy, especially after previous LN pathological confirmation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential role of FDG PET-CT in assessing treatment response after neoadjuvant therapy has been investigated in several studies in variable groups of patients 106 . Despite this, treatment response in NSCLC is still largely assessed with conventional CT. A recent study from Israel evaluating the use of FDG PET-CT to assess the resectability of patients with stage III NSCLC after neoadjuvant therapy reported a very high sensitivity and negative predictive value for detecting responding nodes, which may guide optimal patient selection for curative resection 107 . Another recent study from Korea evaluating a similar patient cohort reported significantly increased relapse-free and overall survival in patients undergoing surgery who showed CMR within mediastinal nodal disease on FDG PET-CT following neoadjuvant treatment compared to incomplete responders 108 .…”
Section: Treatment Response In Lung Carcinomamentioning
confidence: 99%